Neuro-cognitive correlation of memory effectiveness and emotional arousal - Alarabi, Khamis Faraj; Abdul Rahman, Abdul Wahab; Dzulkifli, Mariam Adawiah; Kamaruddin, Norhaslinda (International Society of Computers and Their Applications (ISCA), 2014)
Studies have shown that memory effectiveness can be greatly influenced by emotional arousal. In this paper relationship between EEG-based emotional arousal and memory effectiveness were investigated. The focus of the research work assumed information encoding and information retrieval operations as memory effectiveness. Previous studies indicated a strong correlation between emotions and memory consolidation, while other studies reported crucial role of the amygdala in exerting emotional arousal influences. This role suggested seems to be greater during information encoding than retrieval. In this preliminary study four postgraduate students volunteered to participate in this memory test experiment, and their EEG brain wave signals were captured and recorded during training and testing. The results of processing their brain signals seem to indicate high level of emotional arousal, which may have strong correlation with memory consolidation. The results also support the notion that, the amygdala plays important role during information encoding rather than during information retrieval.